Modern Thought of Islamic Religious Education According to Mahmud Yunus - Ria Putranti Arwitaningsih; Khuriyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article aims to examine and explain the movement of Mahmud Yunus' thoughts on Islamic education. Mahmud Yunus is an Islamic education reformer from Minangkabau. Through his position in the Ministry of Religious Affairs, he advocated and fought for the inclusion of religious education subjects into the national curriculum and supported the implementation of religious education in public schools and the establishment of the National Islamic University (PTAIN). Mahmud Yunus' reform movement in Indonesia is an interesting study that needs to be studied in the context of contemporary Indonesian figures and Mahmud Yunus' perspective on Islamic education and its relation to modern education. The type of research in this study is library research and the data comes from some primary and secondary literature related to Mahmud Yunus' thoughts and their relevance to modern education. This research focuses more on Mahmud Yunus' attention and commitment to the improvement and development of Islamic education which can be seen further in some of his thoughts, among others, in terms of Islamic education, goals, curriculum, teaching methods of educators and institutions of Islamic education institutions.